CCR2 upregulated on peripheral T cells in osteoarthritis but not in bone marrow. (28th October 2018) - Arkestål, Kurt; Mints, Michael; Enocson, Anders; Linton, Ludvig; Marits, Per; Glise, Hans; Andersson, John; Winqvist, Ola
Abstract: Osteoarthritis (OA) is a condition affecting millions of patients around the world, causing pain and disability and often resulting in joint replacement surgery. The aetiology of OA has long been attributed to mechanical wear mainly due to the increased prevalence of OA in load bearing joints among older patients. However, recent studies reveal a complex molecular disease causality in which inflammation, nutritional deficit and angiogenesis lead to the destruction of the joint structure. The aim of this study was to examine chemokine receptor expression in peripheral blood and bone marrow in OA patients. We devised a protocol for extracting healthy bone marrow from patients undergoing hip arthroplasty due to coxarthrosis. Flow cytometry was used to determine the expression of 18 chemokine receptors on CD4 and CD8 T cells from bone marrow and blood from 7 osteoarthritis patients and peripheral blood from 9 healthy controls. We found a significantly increased fraction of CCR2 expressing CD4 and CD8 T cell in peripheral blood compared to healthy controls. Also, there was a significant decrease in CXCR3 (Th1) ( P < 0.01) expressing T cells in peripheral blood from OA patients. Finally, multivariate analysis was used to separate T cell profiles from healthy controls and OA patients and demonstrate that the divergence of chemokine receptor expression occurs in the mature T cell subsets. In conclusion, we find increased CCR2 expression in peripheral blood from OA patients that possibly may be targeted in future clinical studies.